Physician burnout: contributors, consequences and solutions. (24th March 2018) - West, C. P.; Dyrbye, L. N.; Shanafelt, T. D.
Abstract: Physician burnout, a work‐related syndrome involving emotional exhaustion, depersonalization and a sense of reduced personal accomplishment, is prevalent internationally. Rates of burnout symptoms that have been associated with adverse effects on patients, the healthcare workforce, costs and physician health exceed 50% in studies of both physicians‐in‐training and practicing physicians. This problem represents a public health crisis with negative impacts on individual physicians, patients and healthcare organizations and systems. Drivers of this epidemic are largely rooted within healthcare organizations and systems and include excessive workloads, inefficient work processes, clerical burdens, work–home conflicts, lack of input or control for physicians with respect to issues affecting their work lives, organizational support structures and leadership culture. Individual physician‐level factors also play a role, with higher rates of burnout commonly reported in female and younger physicians. Effective solutions align with these drivers. For example, organizational efforts such as locally developed practice modifications and increased support for clinical work have demonstrated benefits in reducing burnout. Individually focused solutions such as mindfulness‐based stress reduction and small‐group programmes to promote community, connectedness and meaning have also been shown to be effective. Regardless of the specific approach taken, the problem of physician burnout is best addressed when viewed as a shared responsibility of both healthcare systems and individual physicians. Although our understanding of physician burnout has advanced considerably in recent years, many gaps in our knowledge remain. Longitudinal studies of burnout's effects and the impact of interventions on both burnout and its effects are needed, as are studies of effective solutions implemented in combination. For medicine to fulfil its mission for patients and for public health, all stakeholders in healthcare delivery must work together to develop and implement effective remedies for physician burnout. Abstract : Click here to view the Editorial Comment by R. Tyssen